Pengaruh Ukuran Perusahaan, Tingkat Hutang, Dan Likuiditas Terhadap Keputusan Hedging Pada Perusahaan Manufaktur Yang Terdaftar Di Burfa Efek Indonesia Tahun 2014-2018 - Novita Afelya Pramudita; Wisnu P Setiyono (International Journal on Orange Technologies, 2021)
Hedging is an alternatief of risk management in dealing with losses that happened to the company which conducts international trade. This study’s purpose is to analyze the influence of firm size, debt level, and liduidity on heging decision in manufacturing companies listed on the Indonesian Stock Exchange in the period 2014-2018. The object of research is manufacturing companies listed on the Indonesia Stock Exchange in the periode 2014-2018 with research samples obtained through purposive sampling as mans as 90 companies were sampled. The data use taken from the secondary financial statement (annual report).data analysis techniques using logistic regression test using SPSS.The results of this study prove that partially firm size and liquidity has an influence on hedging decision. Meanwhile, debt level do not effect hedgibg decision. While that simultaneously variabels firm size, debt level and liquidity has an influence on hedging decision